2009
DOI: 10.1037/a0016231
|View full text |Cite
|
Sign up to set email alerts
|

Examining self-presentation as a motivational explanation for comparative optimism.

Abstract: Five studies examined a self-presentation explanation for comparative optimism. Experiments 1 and 2 laid the foundation for such an account by first showing that people associate a favorable identity-image with the conveyance of an optimistic outlook and that people recognize that an individual may be perceived in a negative light if his or her optimistic estimates are disconfirmed, hence raising the issue of potential accountability demands. Following the issue of accountability, the results across Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
2
39
1
2
Order By: Relevance
“…This explanation for increased overconfidence is in line with the findings of Tyler & Rosier (2009), who found that comparative optimism was linked to motivational efforts in self-presentation. Participants employed comparative optimism only if the circumstances involved little risk of being held accountable for the assessment.…”
Section: Discussionsupporting
confidence: 78%
“…This explanation for increased overconfidence is in line with the findings of Tyler & Rosier (2009), who found that comparative optimism was linked to motivational efforts in self-presentation. Participants employed comparative optimism only if the circumstances involved little risk of being held accountable for the assessment.…”
Section: Discussionsupporting
confidence: 78%
“…While we see promise in these two possible explanations for why people might lean toward optimistic behavior, many other possibilities exist (for additional ideas, see Helweg‐Larsen, Sadeghian, & Webb, ; Krizan & Windschitl, ; Sharot, ; Shepperd, Carroll, Grace, & Terry, ; Taylor & Brown, ; Tyler & Rosier, ).…”
Section: Discussionmentioning
confidence: 94%
“…Unrealistic optimism is a systematic error in predicting one's future, which manifests itself as an individual's tendency to overestimate the frequency with which good events will happen, and to underestimate the frequency with which bad events will happen to oneself in comparison to an average other (Hoch, 1985;Weinstein, 1980). Nevertheless, many researchers propose that unrealistic optimism is adaptive, because optimistic expectations make oneself feel good (Armor, Massey, & Sacket, 2008), and it may enhance the way one is perceived by others (Tyler & Rosier, 2009).…”
Section: Introductionmentioning
confidence: 99%